The startup's guide to sales : how not to crash and burn - Joseph, Roshan Louis (SAGE, 2020)
"ARE YOU A STARTUP? THEN START HERE... From that gleam in your eye, to prototype, to production-you are all set to wow the world with your genius. You take the first step towards your goal and realize that between you and the consumer is a moat full of dragons, demons and turbulence that you must cross to make it to 'Start-up Paradise'. The Start-up's Guide to Sales is a practical book that helps you navigate the perils of wrong selling. This is not sales theory, but a 'tried-out' recipe book for success. Read on and sail the choppy waters with sales savvy!"--